The role of the arbitrator in finding the truth - Bularca Anca Roxana (Bulletin of the Transilvania University of Braşov, 2022)
The study on the role of the arbitrator in finding out the truth aims to highlight the specific elements of the arbitration procedure, considering that it must be carried out with the application and observance of the principles of the civil process dictated by the Code of Civil Procedure for all judicial procedures. The principle of finding the truth, however, has a specific applicability in private jurisdiction proceedings, given that within them a judgment in equity can take place and which differentiates them from the trial procedure before the common law courts. Finding out the truth is the goal of any judicial proceeding and leads to fair justice.